Prevalence of Knee Pain and Its Influence on Quality of Life and Physical Function in the Korean Elderly Population: A Community Based Cross-Sectional Study - Kim, In Je (The Korean Academy of Medical Sciences, 2011)
To investigate the prevalence of knee pain and its influence on physical function and quality of life (QOL), we examined 504 community residents of Chuncheon, aged ≥ 50 yr. Demographic information was obtained by questionnaire, and radiographic evaluations consisted of weight-bearing semi-flexed knee anteroposterior radiographs. Self-reported QOL and function were assessed using the Western Ontario and McMaster Universities Osteoarthritis (WOMAC) Index and Short Form 12 (SF-12). Performance-based lower extremity function was assessed using the tests consisting of standing balance, usual walk and chair stands. The prevalence of knee pain was 46.2% (32.2% in men and 58.0% in women) and increased with age in women. After adjustment of confounders including the presence of knee OA, the subjects with knee pain had significantly worse WOMAC function and SF-12 scores compared to subjects without knee pain. Among the subjects with knee pain, women had worse WOMAC and SF-12 scores than men. Subjects with knee pain had worse physical performance score compared to those without knee pain, especially among females. In conclusion, the prevalence of knee pain is high (32.2% in men and 58.0% in women) in this elderly community population in Korea. Independent of knee OA and other confounding factors, subjects with knee pain have more than 5-fold increase in the risk of belonging to the worst lower extremity function compared to subjects without knee pain.